2020
DOI: 10.1002/brb3.1953
|View full text |Cite
|
Sign up to set email alerts
|

Altered functional activity in bipolar disorder: A comprehensive review from a large‐scale network perspective

Abstract: Background Growing literature continues to identify brain regions that are functionally altered in bipolar disorder. However, precise functional network correlates of bipolar disorder have yet to be determined due to inconsistent results. The overview of neurological alterations from a large‐scale network perspective may provide more comprehensive results and elucidate the neuropathology of bipolar disorder. Here, we critically review recent neuroimaging research on bipolar disorder using a networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 108 publications
4
20
0
Order By: Relevance
“…Diverse BD symptoms involve widespread activation across brain regions, and a network‐based investigation may more comprehensively contribute to understanding the pathology of this disorder (Yoon et al, 2021 ). Neuroimaging studies have implicated dysfunction in emotion regulation networks in BD (Strakowski et al, 2012 ) that has mainly been incorporated into two theories related to brain imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse BD symptoms involve widespread activation across brain regions, and a network‐based investigation may more comprehensively contribute to understanding the pathology of this disorder (Yoon et al, 2021 ). Neuroimaging studies have implicated dysfunction in emotion regulation networks in BD (Strakowski et al, 2012 ) that has mainly been incorporated into two theories related to brain imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously suggested that basal ganglia may play an important role in the dysfunctional emotional processing and regulation of BD patients ( 26 ). Nevertheless, whereas in this study the BGN is highlighted as the FBN that is more functionally abnormal in BD, in the literature it has been demonstrated that some other FBNs appear to be more relevant in BD, such as the default mode, central executive, and salience networks ( 25 ). Our results demonstrate that the ASN seems to be abnormal in BD, but we did not find any significant abnormalities related to executive control networks in our study.…”
Section: Discussionmentioning
confidence: 64%
“…Recently, Yoon et al ( 25 ) did a review study on altered functional connectivity in BD. They suggested that the pathophysiology of BD is influenced by disrupted intranetwork and internetwork functional connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The potential impact of a better understanding of the BOLD signal is far-reaching given that this measure offers noninvasive whole-organ coverage and is widely used across species, thus providing a link between basic research and patient management. Further, there is significant evidence, although much of it is correlative, that brain network measures derived from BOLD contrast (i.e., functional connectivity) may have utility as a diagnostic and prognostic tool for a variety of neurological conditions as well as brain injuries and diseases (see select reviews by Wang et al, 57 Lunkova et al, 58 Harikumar et al, 59 Yoon et al, 60 and Kanel et al 61 ). The combination of fMRI with complementary modes not only helps discern what measures may be most useful clinically but also stands to yield mechanistic insight into the biology that underpins BOLD signal differences between individuals, populations, and time points.…”
Section: Combining Various Modes With Fmrimentioning
confidence: 99%